Full Factorial Experimental Design For Development And Validation Of Rp-Hplc Method For Estimation Of Apixaban In Bulk And Pharmaceutical Formulations (Journal of Pharmaceutical Negative Results, 2022)
According to International Conference on Harmonization (ICH Q8 [R2]) guidelines, QbD approach was implemented forChromatographic method development and its validation. The research work demonstrated that RP-HPLC is valid for the determinationof assay of Apixaban. Experiment was carried out for varying three parameters were extracted by using principal component analysis.Chromatographic separation is achieved on a C-18 column. In development of RP-HPLC method factors like Mobile Phase(Acetonitrile, Methanol, Water, Buffer), mobile phase composition (10-30% v/v) and pH range (5-7) are critical to maintain. HenceCentral Composition factorial design was used as screening model and applied as optimization model for the interaction and quadraticeffects of three factors. Optimization was done according to desirability value. Optimized mobile phase was water: acetonitrile (10:90),7 pH at maximum and Wavelength 277nm. Retention time, asymmetric factor and theoretical plates were found to be 2.9 min, 0.83,3931 respectively. Optimised standard curve showed a regression coefficient is 0.999. The method was validated as per ICH guidelines